2007
DOI: 10.1021/jp0759372
|View full text |Cite
|
Sign up to set email alerts
|

Understanding a Degradation Mechanism of Direct Methanol Fuel Cell Using TOF-SIMS and XPS

Abstract: The catalyst layers, which were obtained from the aged membrane electrode assemblies (MEAs) showing performance loss, 17%, 37%, 45% as compared with that from the pristine MEA were investigated using X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectroscopy (TOF-SIMS) to understand the degradation mechanism of single-cell performance in direct methanol fuel cell. The metallic components in the PtRu anode catalyst layer was decreased significantly with the performance drop reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 29 publications
4
41
1
Order By: Relevance
“…However, the CO tolerance of RuO 2 ns(1.0)-Pt/C is comparable to PtRu/C at elevated temperatures, where PtRu/C stability may become a major issue. The instability of Ru under the fuel cell operation conditions has been reported [20][21][22]. The amount of Ru loss due to dissolution should increase with increasing cell temperature.…”
Section: Co Tolerance Of Ruo 2 Ns-pt/c With Different Ruo 2 Ns Loadingmentioning
confidence: 92%
See 2 more Smart Citations
“…However, the CO tolerance of RuO 2 ns(1.0)-Pt/C is comparable to PtRu/C at elevated temperatures, where PtRu/C stability may become a major issue. The instability of Ru under the fuel cell operation conditions has been reported [20][21][22]. The amount of Ru loss due to dissolution should increase with increasing cell temperature.…”
Section: Co Tolerance Of Ruo 2 Ns-pt/c With Different Ruo 2 Ns Loadingmentioning
confidence: 92%
“…It has been reported that metallic Ru in the PtRu alloy catalyst dissolves as Ru n+ and deposits at the cathode under fuel cell operating conditions, leading to catalyst degradation [20][21][22]. Thus, the stability of RuO 2 ns(0.5)-Pt/C was considered by an accelerated stability test (potential cycling between 0.05-1.2 V vs. RHE in 0.5 M H 2 SO 4 (60°C) at 50 mV s -1 for 1,000 cycles).…”
Section: Stability Of Ruo 2 Ns(05)-pt/c and Pt/cmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the surface properties of the mostly C-based membrane electrodes (229) and its degradation (230,231) during use are of interest. Often special electrochemical cells are used to avoid influence from atmosphere.…”
Section: Energy Applicationsmentioning
confidence: 99%
“…Ru cations in the polymer electrolyte membrane affect its characteristic features, for example, an increase in the number of Ru ions per sulfonic acid group in the membrane decreases the water uptake of the membrane and increases the microviscosity of the fluidic regions possibly due to a change in the free volume of the membrane. Furthermore, Ru ions present in the membrane affect its proton conductivity, and accelerate membrane degradation [6][7][8]. Recently, the effects of catalyst-carbon support on proton conduction have been studied in detail by Liu et al [9].…”
Section: Introductionmentioning
confidence: 99%